2012
DOI: 10.1103/physrevb.85.115109
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Fermi surface and momentum density in heavily doped La2xSrxCuO4

Abstract: We have observed the bulk Fermi surface (FS) in an overdoped (x=0.3) single crystal of La2−xSrxCuO4 by using Compton scattering. A two-dimensional (2D) momentum density reconstruction from measured Compton profiles yields a clear FS signature in the third Brillouin zone along [100]. The quantitative agreement between density functional theory (DFT) calculations and momentum density experiment suggests that Fermi-liquid physics is restored in the overdoped regime. In particular the predicted FS topology is foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 81 publications
(66 reference statements)
1
6
0
Order By: Relevance
“…The quantitative agreement between DFT calculations and momentum density experiments (2D ACAR and 2D Compton scattering reconstruction) shown in Ref. [12] suggests that Fermi liquid physics is restored in the overdoped regime. A FS signal was also clearly observed by Compton scattering in the third Brillouin zone along [100] and the calculated FS topology was found to be in good accord with the corresponding experimental data.…”
Section: X-ray Compton Scattering Spectroscopysupporting
confidence: 54%
See 1 more Smart Citation
“…The quantitative agreement between DFT calculations and momentum density experiments (2D ACAR and 2D Compton scattering reconstruction) shown in Ref. [12] suggests that Fermi liquid physics is restored in the overdoped regime. A FS signal was also clearly observed by Compton scattering in the third Brillouin zone along [100] and the calculated FS topology was found to be in good accord with the corresponding experimental data.…”
Section: X-ray Compton Scattering Spectroscopysupporting
confidence: 54%
“…The AGP and RVB calculations have shown that the deviation from integer occupancy becomes stronger as correlations grow. However, the important finding of our recent work in an overdoped (x = 0.3) single crystal of La 2−x Sr x CuO 4 [12] is that strong correlation effects that ordinarily reduce the Compton anisotropy amplitudes are no longer effective at this doping. The quantitative agreement between DFT calculations and momentum density experiments (2D ACAR and 2D Compton scattering reconstruction) shown in Ref.…”
Section: X-ray Compton Scattering Spectroscopymentioning
confidence: 88%
“…This might explain an important finding of Ref. that the correlations that ordinarily reduce the Compton anisotropy amplitudes are no longer effective in La 1.7 Sr 0.3 CuO 4 .…”
Section: Discussionmentioning
confidence: 93%
“…It leads to weakening of the momentum dependence of the enhancement until its disappearance when there are high contributions of HMC. Therefore, in such materials, in which lattice effects are strong, IPM describes e–p densities quite well (as, e.g., in Y or observed lately in overdoped cuprate superconductors ).…”
Section: Many‐body Effectsmentioning
confidence: 83%
“…First, the TPMD of an oriented Fe 2 TiSn single crystal with the integration axis along [100] was measured at the positron beam facility POSH at the Reactor Instituut of the Delft University of Technology [8,9]. The sample was aligned with the aid of single crystal Xray diffraction.…”
Section: Measurementsmentioning
confidence: 99%